2010
DOI: 10.1177/230949901001800306
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thromboprophylaxis for Patients Undergoing Hip Fracture Surgery

Abstract: Routine use of mechanical thromboprophylaxis is recommended in patients undergoing hip fracture surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“… 22 24 25) There have been a few reports on preventive effect of IPC in Asians. Sugano et al 14) and Yokote et al 16) reported its effectiveness in Japanese people, Mehta et al 15) in Singapore people, and Jo et al 17) in Korean people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 24 25) There have been a few reports on preventive effect of IPC in Asians. Sugano et al 14) and Yokote et al 16) reported its effectiveness in Japanese people, Mehta et al 15) in Singapore people, and Jo et al 17) in Korean people.…”
Section: Discussionmentioning
confidence: 99%
“… 13) Therefore, mechanical methods using intermittent pneumatic pumps have been gaining popularity, and variable results on their effectiveness have been reported in Asian countries. 14 15 16 17) …”
mentioning
confidence: 99%
“…Elderly patients undergoing HFS are at higher risk of VTE owing to associated immobility along with other risk factors [ 1 , 2 , 17 ]. The immobility due to severe hip pain during the preoperative period may cause venous stasis from the lower extremities, thus increasing the risk of VTE in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In hip fracture surgery, mechanical VTE prophylactic methods can reduce the incidence of VTE [ 38 ]. In a study by Mehta et al, the authors showed that using an IPCD for ≥20 h per day before and after surgery could reduce VTE in 434 hip fracture patients.…”
Section: Statements Of Group 2: Mechanical Venous Thromboembolism Prophylaxismentioning
confidence: 99%
“…In a study by Mehta et al, the authors showed that using an IPCD for ≥20 h per day before and after surgery could reduce VTE in 434 hip fracture patients. The incidence of DVT was 11 (2.5%) and that of PE was 2 (0.5%) [ 38 ], compared with a previous study, which showed an incidence of DVT of 8% in 104 elderly hip fractures without mechanical thromboprophylaxis [ 39 ]. However, there are inadequate data for fatal PE and mortality rates to make a conclusion.…”
Section: Statements Of Group 2: Mechanical Venous Thromboembolism Prophylaxismentioning
confidence: 99%